Preliminary Assessment of Tuff as CO2 Sorbent. (July 2017) - Ammendola, P.; Raganati, F.; Chirone, R.; Miccio, F.
Abstract: The removal of carbon dioxide from flue gases can be achieved through adsorption separation technologies. In this framework, zeolites have shown promising results for the separation of CO2 from gas mixtures and can potentially be used for both TSA/PSA processes. In particular, natural zeolites are inexpensive and can be viable sorbents. The aim of this work is the characterization of a non-synthetic tuff zeolite that could be used as carbon dioxide adsorbent. In order to assess changes in its structural and gas adsorption properties, the tuff was treated with acid solutions. Both the natural and acid treated samples were fully characterized from a chemico-physical point of view: pore size distribution, specific surface, SEM and XRD analyses were performed. The CO2 adsorption capacity of the samples was measured in a lab-scale fixed bed reactor. Breakthrough curves were determined at a fixed flow rate (15Nl/h) using mixtures of CO2 and N2 with different CO2 concentrations (5-20%vol.). Then, the adsorption isotherms were obtained from experimental data. The experimental results show that tuff, in particular if properly pre-treated, is a promising alternative to synthetic zeolites in adsorption processes for CO2 removal.